A growing fear: Prevalence of nomophobia among Turkish college students. (November 2016) - Yildirim, Caglar; Sumuer, Evren; Adnan, Müge; Yildirim, Soner
The purpose of the present study was to investigate the prevalence of nomophobia (the fear of being out of mobile phone contact) among young adults in Turkey. The Nomophobia Questionnaire (NMP-Q) was administered to 537 Turkish college students. The results revealed 42.6% of young adults had nomophobia, and their greatest fears were related to communication and information access. The study also found that gender and the duration of smartphone ownership had an effect on young adults' nomophobic behaviors, whereas age and the duration of mobile phone ownership had no effect. Based on these results, implications, limitations, and further studies were discussed.